Integrasi Ekonometri dalam Efektivitas Perencanaan menuju Penyediaan Perumahan yang Berkelanjutan: Econometric Integration in Planning Effectiveness toward Sustainable Housing Provision - Dian Rahmawati; Ikhfadhulhikmy Kurnia; Mulyono Sadyohutomo (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2022)
In accelerating spatial planning, an effective instrument is needed in planning so that the implementation of space utilization is in accordance with the expected goals, so that resources remain efficient, investment calculations become more real, and environmental balance in sustainable urban development is maintained. Housing development is often delayed (planning delay) due to the inefficient land provision process. On the other hand, the housing backlog is increasing to 800,000 units per year, thus it is necessary to investigate the effectiveness of planning, especially in the housing sector that has been running in Indonesia. Econometry as a quantitative approach with various variances of analysis techniques has many benefits but has not been widely integrated in planning, especially in calculating the effectiveness of instruments in achieving spatial planning goals. This article aims to examine the effectiveness of planning, especially related to land value and housing development through an econometric model approach by taking samples in Surabaya. The technique used is multiple regression analysis which shows the level of influence between six independent variables, namely land area, building area, land value, land price increases, property prices, and property taxes on the dependent variable, namely the effectiveness of planning indicated in the form of time required to implement the plan. The results show that there are 3 variables of the 6 independent variables that are proven to have an influence based on their significance value, namely land area, land value, and the percentage of increase in land value. Based on the regression results, it takes an average of -0.274 years to be constant, if other variables are considered absent, or it is interpreted that the phenomenon of housing development tends to precede or independent of housing planning in the sectoral plans and spatial plans.